Hadis-Hadis Tentang Jual Beli Gharar dan Bentuknya Pada Masa Kontemporer - Yenni Samri Juliati Nasution; Ardiansyah Ardiansyah; Heri Firmansyah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Hadiths about Gharar in Buying and Selling and the Forms in the Contemporary PeriodThis article examines various hadith (traditions) which talk about the issue of gharar sale (uncertain sale). The research finds out that there are dozens of hadiths which are then reduced to 5 hadiths considered to be representative and focus of the discussion, both in terms of the matn and sanad. This research is thematic, namely the hadiths related to gharar law with sanad and matn criticism approach to get a clear picture of the authenticity of the hadiths understudied. To get a comprehensive understanding of the issue of gharar sale, this paper also develops the research on the form of gharar sale in the contemporary era with a fiqh perspective which is also supported by the arguments found in the Quran. The research finds out that the hadiths which talk about the issue of gharar are categorized as sahih (authentic) with various criteria and therefore can be used as evidence (hujjah) in the making of legal decisions based on Islamic law (istinbath).